Dietary salt restriction during conservative therapy may prevent declines in residual renal function for the first year after starting peritoneal dialysis in patients with end-stage end- stage renal diseases. Issue 1 (2020) - Hiramatsu, Tetsuaki; Katsuno, Takayuki; Nakamura, Tomohiro; Mizuno, Masashi; Suzuki, Yasuhiro; Kosugi, Tomoki; Nomori, Sumiyo; Maruyama, Shoichi; Shiga, Yoshiko; Koyama, Tomio; Sun, Ting
No abstract available